Pelatihan Kewirausahaan dan Strategi Pemasaran Produk Hasil Kerajinan Kelompok PKK pada Desa Wisata Sungai Kupah Kabupaten Kubu Raya - Lestari, Melati Pramudita; Widodo, Agus; Cahyowati, Anik; Wana, Desty; Fiorintari, Fiorintari; Triani, Merry; Rukmi, Murti Puspita; Andriana, Susan; Sari, Arindya; Nugroho, Yohanes Adi (Kapuas, 2023)
The purpose of implementing this community service is to provide training and empower the community regarding the importance of entrepreneurial management and marketing strategies for the products of the PKK group's work in the Sungai Kupah tourist village. This community service activity is carried out by providing material on entrepreneurship and providing an understanding that the community can market handicraft products and make their living environment a tourist destination. The results of this activity the participants were able and able to market handicraft products by utilizing existing digital marketing and were able to describe what potentials existed in Sungai Kupah Tourism Village, Kubu Raya Regency.